2018
DOI: 10.1111/trf.14559
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year trends in perioperative red blood cell transfusion from index cases in five surgical specialties: 2011 to 2015

Abstract: RBC transfusion appears to be decreasing across multiple surgical specialties, with no apparent increase in myocardial infarctions or renal failure. This likely represents an important improvement in patient care. Continued efforts are needed to develop patient blood management programs and further reduce RBC transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…First, routine transfusion patterns revealed the idea of restrictive transfusion has already been embraced in clinical practice even 2‐3 years before publication of the new standard, with a much higher uptake compared with liberal practice. This is in line with foreign reports and can reinforce our confidence towards the roles played by the growth of transfusions evidence and guidelines. Second, however, one‐fifth of RBCs were still transfused at Hb ≥10 g/dl after our previous investigation in 2006–2009 .…”
Section: Discussionsupporting
confidence: 88%
“…First, routine transfusion patterns revealed the idea of restrictive transfusion has already been embraced in clinical practice even 2‐3 years before publication of the new standard, with a much higher uptake compared with liberal practice. This is in line with foreign reports and can reinforce our confidence towards the roles played by the growth of transfusions evidence and guidelines. Second, however, one‐fifth of RBCs were still transfused at Hb ≥10 g/dl after our previous investigation in 2006–2009 .…”
Section: Discussionsupporting
confidence: 88%
“…The transfusion rate for those undergoing cardiac surgery is likely to be increased or stationary, whereas it is decreased in orthopedic, neurogeneral, and gynecologic surgeries. 10,11 The association between RBC transfusion and adverse clinical outcomes in patients undergoing cardiac surgery has been well studied in retrospective analyses. 4,7,[12][13][14][15] However, there is a lack of evidence regarding the risk of RBC transfusion during heart valve surgery.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…The transfusion rate for those undergoing cardiac surgery is likely to be increased or stationary, whereas it is decreased in orthopedic, neurogeneral, and gynecologic surgeries. 10,11…”
mentioning
confidence: 99%
“…111 PBM strategies have led to a substantial decline in blood transfusion in many developed countries over the past 5 years. [112][113][114][115][116][117][118][119][120] In parallel with reduction in blood transfusion, recent active surveillance studies of TACO and TRALI found lower incidence rates of transfusion-related adverse events. 5,9 Future directions…”
Section: Mitigationmentioning
confidence: 99%